Pengaruh Likuiditas, Profitabilitas, Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan Corporate Social Responsibility Sebagai Variabel Moderasi Pada Perusahaan Property Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2016-2022 - Verina Putri, Nesia; Suryani, Yani; Ika, Desi (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
This research was conducted with the aim of knowing the effect of liquidity, profitability and firm size on firm value with Corporate Social Responsibility as a moderating variable. This type of research is a quantitative research that is associative in nature. The population used in this study are property and real estate companies listed on the Indonesia Stock Exchange (IDX) in the period of 2016-2022. The sampling techniques used purposive sampling method with samples of 15 companies over 7 years of observation so that total observation datas are 105 datas. This method of research analysis is statistical analysis using version 26 of SPSS software and Moderated Regression Analysis (MRA). The results of this research indicates that liquidity had no significanlyt effect on firm value, profitability had a significant effect on firm value, firm size had no effect on firm value,Corporate Social Responsibility moderates but is no significant the relationship between liquidity on firm value, and Corporate Social Responsibility did not moderate the relationship between profitability and firm size on firm value in property and real estate companies listed on the Indonesia Stock Exchange (IDX) in period of 2016-2022.